Evaluation of the recombinant protein Sh-TSP-2 for the serological diagnosis of imported urogenital schistosomiasis and comparison with commercially available tests - María Pilar Luzón-García; Laura Navarro; Esther Rodríguez; Manuel Jesús Soriano-Pérez; José Vázquez-Villegas; María Isabel Cabeza-Barrera; Alex Loukas; Nerea Castillo-Fernández; María Jesús Perteguer; Javier Sotillo; Joaquín Salas-Coronas (Parasitology)
Different agencies have emphasized the need to evaluate current serological methods for screening patients with suspected urogenital schistosomiasis. However, there is still a lack of evidence regarding the most appropriate methods for this purpose. Here we assessed the diagnostic efficacy of a newly developed serological technique that utilizes the recombinant protein Sh-TSP-2, applied to the urine and serum of migrants suspected of having urogenital schistosomiasis. The sensitivity, specificity, positive and negative predictive values of an in-house enzyme-linked immunosorbent assay (ELISA) using the recombinant protein Sh-TSP-2 were analysed and compared with other commercial serological methods. Due to the limitations of microscopy as a perfect reference method, a latent class analysis (LCA) and composite reference standard (CRS) approach was used to determine the sensitivity and specificity of each test. According to the LCA model, the commercial tests NovaLisa® and immunochromatography test (ICT) immunoglobulin G–immunoglobulin M (IgG–IgM) presented the highest sensitivity (100%), whereas the Sh-TSP-2 serum ELISA test had 79.2%. The Sh-TSP-2 urine and serum ELISA tests had the highest specificities among the serological methods (87.5 and 75%, respectively). CRS modelling showed that the ICT IgG–IgM, NovaLisa® and Sh-TSP-2 serum tests led in sensitivity at 97.1, 88.6 and 71.4%, respectively, with all tests except that the ICT IgG–IgM test having a specificity >90%. Sh-TSP-2 has been validated as a screening tool for patients suspected of having urogenital schistosomiasis. Although commercial serological tests have shown higher sensitivities, Sh-TSP-2 could be valuable for confirming results from tests with lower specificity. Nevertheless, further studies with larger patient cohorts are necessary to fully verify its potential.